DEPOSITIONAL ENVIRONMENT OF THE SAROLANGUN COALS, SOUTH SUMATRA BASIN - Asep Kurnia Permana; Hermes Panggabean (Jurnal Geologi dan Sumberdaya Mineral, 2011)
The Muaraenim Formation, a Late Miocene unit within the South Sumatera Basin, is included in some of the most significant coal resources in Indonesia. The upper part of the unit exposed in the Sarolangun Region, where it consists mainly of sandstone and shale, with relatively thin (< 1.5 m) coal beds. Lithofacies analysis of the outcropping strata indicates that deposition took place in a terrestrial to marine environment. Microscopic analysis shows that the coal consists mainly of vitrinite maceral group (telovitrinite and detrovitrinite), with having a rare to sparse inertinite and minor liptinite and mineral matter. Palynological studies show abundant pollens, derived from mangrove vegetation that grew in a fresh water environment. The GI and TPI values, calculated from detailed maceral analysis, when plotted on similar diagrams to those developed by Diessel (1992) show the coals to have two different facies characteristics. Some of the coals, especially those having a high vitrinite content, show high TPI and relatively high GI values, suggesting that deposition was in upper delta plain and fluvial environments (wet forest swamp) with a relatively high rate of subsidence. Other coals have much lower TPI but higher GI values, indicating that peat was possibly developed in in a lower delta plain, with relatively slow subsidence conditions. Some coal samples also have high proportions of pyrite and other mineral matter, and thus it might have been deposited in more brackish environments. The change reflects the onset of marine transgression near the top of the Muara Enim sequence. Palynological analysis indicates the occurrence of fresh water and mangrove vegetation, supporting deposition in wet and possibly partly brackish conditions.Keywords: Depositional environment, Sarolangun coals, South Sumatera Basin, Indonesia